2023
DOI: 10.1039/d2na00835a
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale insights into the epitaxial growth mechanism of 2D Cr3Te4 on mica

Abstract: Two-dimensional (2D) magnetic materials are of wide research interest owing to their promising applications in spintronic devices. Among them, chromium chalcogenide compounds are one of the limited available systems that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…[20][21][22][23] Such a chemical reaction process, occurring on the surface of 3D-metals, often allows chemical interaction with the surrounding vapor phase environment that induces the formation of a second phase suitable for multifunctional applications. [24][25][26][27] For instance, a highly ordered 1D intermediate crystal was observed between the MoO 2 substrate and the product 2D MoS 2 obtained through thermal sulfidation, and the subsequent thickening of MoS 2 caused a transition from a p-type to an n-type Schottky contact. 28 Our previous work demonstrated that a S-rich environment resulted in an unconventional Au 4 S 4 reconstructed phase at the interface of the Au substrate and 2D MoS 2 during the growth of MoS 2 on 3D nanoporous gold (NPG).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Such a chemical reaction process, occurring on the surface of 3D-metals, often allows chemical interaction with the surrounding vapor phase environment that induces the formation of a second phase suitable for multifunctional applications. [24][25][26][27] For instance, a highly ordered 1D intermediate crystal was observed between the MoO 2 substrate and the product 2D MoS 2 obtained through thermal sulfidation, and the subsequent thickening of MoS 2 caused a transition from a p-type to an n-type Schottky contact. 28 Our previous work demonstrated that a S-rich environment resulted in an unconventional Au 4 S 4 reconstructed phase at the interface of the Au substrate and 2D MoS 2 during the growth of MoS 2 on 3D nanoporous gold (NPG).…”
Section: Introductionmentioning
confidence: 99%